2022
DOI: 10.3390/cells11121883
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Actively Contribute to Obesity-Associated Inflammation and Pathological Complications

Abstract: Obesity is characterized by an increase in body weight associated with an exaggerated enlargement of the adipose tissue. Obesity has serious negative effects because it is associated with multiple pathological complications such as type 2 diabetes mellitus, cardiovascular diseases, cancer, and COVID-19. Nowadays, 39% of the world population is obese or overweight, making obesity the 21st century epidemic. Obesity is also characterized by a mild, chronic, systemic inflammation. Accumulation of fat in adipose ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 245 publications
1
32
0
Order By: Relevance
“…Furthermore, the humoral immune response is defective in obese individuals, and B lymphocytes in obese individuals express a proinflammatory phenotype that reduces their ability to optimally respond to infection (44). Obesity or high-fat diets modify the composition of the gut microbiota and increase intestinal permeability, leading to the passage of bacteria and bacterial produc ts (e.g., lipopolysaccharides, LPS) across the intestinal barrier into the circulation, which can activate innate immune cells and immune signaling pathways and contribute to inflammation formation (2,44,(60)(61)(62)(63). In addition, a high-fat diet increases the proportion of gramnegative bacteria, further promoting the absorption of LPS across the intestinal barrier (60, 64).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the humoral immune response is defective in obese individuals, and B lymphocytes in obese individuals express a proinflammatory phenotype that reduces their ability to optimally respond to infection (44). Obesity or high-fat diets modify the composition of the gut microbiota and increase intestinal permeability, leading to the passage of bacteria and bacterial produc ts (e.g., lipopolysaccharides, LPS) across the intestinal barrier into the circulation, which can activate innate immune cells and immune signaling pathways and contribute to inflammation formation (2,44,(60)(61)(62)(63). In addition, a high-fat diet increases the proportion of gramnegative bacteria, further promoting the absorption of LPS across the intestinal barrier (60, 64).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of peripheral innate immune function were documented in individuals with obesity without an infection, mainly, characterized by non-classical monocytes 19 , NK cells with impaired cytotoxic and imbalanced expression of activating and inhibiting receptors 20 , and increased N/L ratio with a predominance of in ammatory activity by neutrophils compared to non-obese individuals 21 . Accordingly, this present study revealed a distinct peripheral innate immune pro le in severe COVID-19 patients with obesity marked by lower circulating monocytes expressing high levels of suppressive PD-L1, higher frequency of peripheral NK cells, and HD neutrophils, the latter demonstrating an increased in ammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this increase of NK cells in our population with obesity was strongly and positively associated with the N/L ratio. An increase in this severity biomarker indicates a higher in ammatory response and it is implicated not only in infection diseases 35 , but obesity-associated features may also affect the N/L ratio 21 . In COVID-19, NK cells function, measured by the expression of granzymes and perforins was in uenced by higher levels of IL-6 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, BMI is directly related to WBC counts. This can be ascribed to the fact that obesity can cause an inflammatory condition in the body [19]. Adipose tissue has been shown to increase the production of granulocytes in bone marrow by releasing inflammatory cytokines, such as TNFα, as well as interleukins 1 and 8 [20].…”
Section: Discussionmentioning
confidence: 99%